Financing health in sub-Saharan Africa 1990-2050: Donor dependence and expected domestic health spending. - Angela E Apeagyei; Brendan Lidral-Porter; Nishali Patel; Juan Solorio; Golsum Tsakalos; Yifeng Wang; Wesley Warriner; Asrat Wolde; Yingxi Zhao; Joseph L Dieleman; Justice Nonvignon (PLOS Global Public Health, 2024)
In 2021, global life expectancy at birth was 74 years whereas in sub-Saharan Africa it was 66 years. Yet in that same year, $92 per person was spent on health in sub- Saharan Africa, which is roughly one fifth of what the next lowest geographic region-North Africa and Middle East-spent ($379). The challenges to healthy lives in sub-Saharan Africa are many while health spending remains low. This study uses gross domestic product, government, and health spending data to give a more complete picture of the patterns of future health spending in sub-Saharan Africa. We analyzed trends in growth in gross domestic product, government health spending, development assistance for health and the prioritization of health in national spending to compare countries within sub-Saharan Africa and globally.We found that while gross domestic product was projected to increase through 2050 in sub-Saharan Africa, the share of gross domestic product that goes to health spending is only expected to increase moderately. Our exploration shows that this tepid growth is expected because the percent of overall government spending that is dedicated to health 7·2% (6·3-8·3) compared to average of 12·4% (11·7-13·2) in other regions) is expected to stay low. Even if the amount, of resources provided from donors climbs some, it is not expected to keep pace with growing economies in sub-Saharan Africa and may transition towards other global public health goods. Critically, development assistance for health provided to sub-Saharan Africa is expected to decrease in some countries, and the expected growth in government health spending might not be enough to cover this expected decline. Increases in spending with a concordant prioritization of health and the appropriate health system governance and structural reforms are critical to ensure that people who live in sub-Saharan Africa are not left behind.